Infarct location is associated with quality of life after mild ischemic stroke. Issue 8 (October 2018) - Lin, Chen; Sangha, Rajbeer; Lee, Jungwha; Corado, Carlos; Jalasutram, Anvesh; Chatterjee, Neil; Ingo, Carson; Carroll, Timothy; Prabhakaran, Shyam
Background: In patients with mild ischemic stroke, small but eloquent infarcts may have devastating effects, particularly on health-related quality of life. Aim: This study investigates the association between acute infarct location and three-month health-related quality of life in patients with mild ischemic stroke. Methods: We evaluated consecutively enrolled patients from a single center between August 2012 and July 2013. Our primary outcome at three months was impairment in any health-related quality of life domain (upper extremity, lower extremity, executive function, and general concerns) defined by a T-score <45. We analyzed the association between acute infarct locations and impaired health-related quality of life at three months in univariate and multivariable analysis. Results: Among 229 patients (mean age 64.9 years, 55% male, 29.7% black, and median initial NIHSS score 1), impaired health-related quality of life was noted in 84 (36.2%) patients at three months. In univariate analysis, patients with subcortical infarcts (56.0% vs. 39.3%, p = 0.02) and brainstem infarcts (21.4% vs. 10.3%, p = 0.02) were more likely to have impaired health-related quality of life. In multivariable analysis, patients with subcortical and/or brainstem infarcts had increased odds of impaired health-related quality of life (adjusted OR 2.54, 95% CI 1.29–5.01, p = 0.01). Conclusions: After mild ischemic stroke, subcortical and brainstem infarct locations predict impairment in health-related quality of life.